18th International Conference of the North American Fuzzy Information Processing Society - NAFIPS (Cat. No.99TH8397)
DOI: 10.1109/nafips.1999.781695
|View full text |Cite
|
Sign up to set email alerts
|

FULSOME: a fuzzy logic modeling tool for software metricians

Abstract: There has been a growing body

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Although their published empirical analyses are not extensive (given the early stage of the research), their work does highlight the significant potential in fuzzy logic modeling when applied to aspects of software project management. Our own work (Gray and MacDonell 1997b;MacDonell et al 1999) has similarly indicated the applicability of fuzzy logic methods to this domain -one of the aims of the work described here is to provide empirical evidence in support of this.…”
Section: Modeling Aspects Of Software Project Managementmentioning
confidence: 63%
See 1 more Smart Citation
“…Although their published empirical analyses are not extensive (given the early stage of the research), their work does highlight the significant potential in fuzzy logic modeling when applied to aspects of software project management. Our own work (Gray and MacDonell 1997b;MacDonell et al 1999) has similarly indicated the applicability of fuzzy logic methods to this domain -one of the aims of the work described here is to provide empirical evidence in support of this.…”
Section: Modeling Aspects Of Software Project Managementmentioning
confidence: 63%
“…The clustering and rule extraction activities were undertaken using the CLUESOME (CLUster Extraction for SOftware MEtrics) component of our FUZZYMANAGER toolset (MacDonell et al 1999). After experimenting with various membership function shapes we restricted ourselves to trapezoidal and triangular as being appropriate for the discrete data being modeled (Kumar et al 1994).…”
Section: Fuzzy Modelingmentioning
confidence: 99%
“…MacDonell et al [21] explored an expert knowledgebased application of FL to effort prediction. This particular research has evolved into the development of a tool, FULSOME, to assist project managers in making predictions.…”
Section: Non-algorithmic Modelsmentioning
confidence: 99%
“…That is to say, most of the work on these modeling methods, including studies undertaken by the authors [13,14,33,34], has been carried out by researchers rather than practitioners, much of it without any definitive sense of the likely acceptability of such methods in an industrial software development setting [11]. For instance, while the alternative of using qualitative labeling for variables as utilised in fuzzy logic methods has been suggested in research (e.g.…”
Section: Introductionmentioning
confidence: 99%